Pharmacological Evaluation of Novel Triazole Derivatives: Synthesis, Docking, and Biological Studies - Shirish Inamdar (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study investigates the pharmacological properties of novel triazole derivatives synthesized through a detailed chemical process. Computational docking studies were employed to predict their potential interactions with biological targets, and biological assays were conducted to assess their efficacy, yielding promising results in various assays, indicating potential therapeutic applications. Triazole derivatives are pivotal in medicinal chemistry due to their diverse pharmacological activities, and this study focuses on novel derivatives synthesized with the aim of exploring their pharmacological potential through synthesis, computational docking, and biological evaluation, which are crucial for identifying lead compounds for drug development. Novel triazole derivatives were synthesized using established chemical methods, with structural characterization performed using spectroscopic techniques. Computational docking studies were conducted to predict their binding affinity and interactions with target proteins, and biological evaluation included in vitro assays to assess their activity against specific biological targets. The synthesis of novel triazole derivatives yielded compounds with confirmed structures, and docking studies revealed potential binding modes and interactions with biological targets. Biological assays demonstrated significant activity against targeted enzymes and receptors, highlighting their pharmacological potential in therapeutic development. The synthesized triazole derivatives show promising pharmacological activities as evidenced by computational docking and biological evaluations, and further optimization and detailed mechanistic studies are warranted to advance these compounds toward clinical application, underscoring the importance of structure-activity relationship studies in drug discovery and development.